A hybrid scheme for wireless physical layer security based on encryption and channel pre-compensation - Tahir, Mohammad; Siddiqi, Mohammad Umar (Taylor & Francis, 2014)
In this paper, a new hybrid scheme for physical layer security based on encryption and wireless channel pre-compensation is proposed. The security is provided by transforming the basic signal constellation into a higher order signal constellation with the help of conventional encryption method (symmetric key encryption) and then using channel knowledge (i.e. amplitude and phase variation), which is location specific, to distort the constellation of encrypted data before transmission. Since detection and demodulation are based upon the known signal constellation, which is not known in advance in our case, it becomes difficult for the eavesdropper to determine the original signal constellation due to the combined effect of encryption and pre-compensation. Using BER as performance metric it is found that the eavesdropper suffers from high BER as compared to its legitimate counterpart hence providing secure communication.